Estudo comparativo entre diabetes tipo 1 e tipo 2 no desenvolvimento de hipoalgesia induzida pelo diabetes na articulação temporomandibular de ratos : Comparative study between type 1 and type 2 diabetes in the development of diabetes induced hypoalgesia in the temporomandibular joint of rats - Muzilli Junior, Augusto, 1952- (2019)
Orientador: Michelle Franz Montan Braga Leite